Relationship of Vit D deficiency with obesity, metabolic abnormalities and Insulin resistance in patients with POS - Safoora Anjum, Amina Saleem, Shazia Noor, Arjumand Mahmood, Salma Khalid, Asma Sarwa (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Polycystic ovary syndrome (PCOS) is the leading endocrine disorder that affects women in their reproductive age with global prevalence of 6 to 26%. Many different studies have established a firm relationship between levels of vitamin D and various symptoms of PCOS that includes subfertility, cycle regulation, insulin resistance and hirsutism. Aim: To validate the correlation of insulin resistance and obesity with vitamin D deficiency in women suffering with PCOS. Methodology: A cross-sectional study was conducted including 110 PCOS patients. Anthropometric measures, demographics details, dietary and menstrual history were collected from the patients. Blood samples were also collected and analyzed for parameters of biochemical and hematological nature along with its hormone profile. All the data was analyzed statistically. Results: Low Levels of vitamin D were observed to be greater in people considered overweight/obese as per their BMI. . The vitamin D deficient patients had significantly higher body weight (p = 0.05), BMI (0.01), testosterone (p = 0.03), LH (p=0.03) and serum calcium (p <0.0001). Univariate correlation analysis among all the important parameters and 25-hydroxyvitamin D revealed no significant correlation. Conclusion: Vitamin D deficiency is quite commonly observed in patients dealing with PCOS and aggravates the abnormalities related to metabolism. For the prevention of adverse consequences, screening of PCOS patients for deficiency of 25-hydroxyvitamin D holds importance so that a suitable replacement therapy can be initiated.